Analisis Tingkat Penerapan Manajemen Pengetahuan Dalam Membangun Organisasi Berbasis Pengetahuan (Studi Kasus PT Trubus Mitra Swadaya SE-JABODETABEK) - Esthi, Raniasari Bimanti; Sukmawati, Anggraini (IPB University, 2011)
PT Trubus Mitra Swadaya is a company engaged in the agribusiness industry that sells a wide range of agricultural goods. The development of the agribusiness industry, particularly agricultural stores are now increasing to fiercer competition. The objectives of this research were (1) Identify the level of knowledge management at PT Trubus Mitra Swadaya, (2) Identify the level of the activities associated with knowledge management at PT Trubus Mitra Swadaya, and (3) Analyzing the perceptions of employees regarding the application of knowledge management at PT Trubus Mitra Swadaya. The data that used in this research were primary data and secondary data. Collecting the respondences was done by quota sampling technique, database examine was done by descriptive analysis, average value calculation analysis, and chi-square analysis.The result of average value calculation analysis showed level implementation of knowledge management was excellent (67,01%), represented from strongly agree answered 20,75% and agree answered 46,26%. Moreover, employees said bad, represented from less agree answered 19,97% and disagree 13,02%. In this research, found at least two components which employees feel valued and still yet to be repaired, that was 1) knowledge and 2) work time. The result average value calculation showed level of activity associated with knowledge management was less good (42,78%), represented five to ten times answered 22,78% and more than ten times 20%. Moreover, employees answered never 30% and less than five times 20%. The result chi-square showed employees’ perception about knowledge management based on employee characteristics where the majority of employees agreeing with the implementation of knowledge management.